2008
DOI: 10.1902/jop.2008.070397
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Extraction Sockets Based Upon Soft and Hard Tissue Components

Abstract: The extraction socket classification proposed here is an objective and helpful tool for socket assessment and for promoting future implant esthetics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
78
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(79 citation statements)
references
References 32 publications
0
78
0
1
Order By: Relevance
“…As previously reported [16] the comparative clinical results between the three experimental groups, showed that at 4 months re-entry surgery, extraction sockets without severe walls deficiencies and with vestibular bone thickness ≥ 1.5 mm, grafted with porcine-derived bone and/or covered by collagen membrane have significantly lower vertical and horizontal bone changes compared to extraction sockets left to heal spontaneously. In addition, in type 1 premolar extraction sockets, based on Juodzbalys et al classification [19], with vestibular bone thickness ≥ 1.5 mm, the use of collagen membrane alone showed similar clinical results to the use of collagen membrane combined with bone graft. Outcomes of the present histological and histomorphometric investigation confirmed the reported clinical data, and indicated that a collagen membrane with low rate of resorbtion (12/14 weeks) may be used alone in extraction socket preservation procedures of sites without severe wall defects, and with a vestibular bone thickness > 1.5 mm.…”
Section: Discussionmentioning
confidence: 97%
“…As previously reported [16] the comparative clinical results between the three experimental groups, showed that at 4 months re-entry surgery, extraction sockets without severe walls deficiencies and with vestibular bone thickness ≥ 1.5 mm, grafted with porcine-derived bone and/or covered by collagen membrane have significantly lower vertical and horizontal bone changes compared to extraction sockets left to heal spontaneously. In addition, in type 1 premolar extraction sockets, based on Juodzbalys et al classification [19], with vestibular bone thickness ≥ 1.5 mm, the use of collagen membrane alone showed similar clinical results to the use of collagen membrane combined with bone graft. Outcomes of the present histological and histomorphometric investigation confirmed the reported clinical data, and indicated that a collagen membrane with low rate of resorbtion (12/14 weeks) may be used alone in extraction socket preservation procedures of sites without severe wall defects, and with a vestibular bone thickness > 1.5 mm.…”
Section: Discussionmentioning
confidence: 97%
“…The extraction socket evaluation was made according to the classification suggested by Juodzbalys et al [34] (Table 1), i.e. socket type 1: adequate extraction socket; socket type 2: compromised extraction socket; socket type 3: deficient extraction socket.…”
Section: Methodsmentioning
confidence: 99%
“…14,20,21 In this study, bone thickness was measured starting at 3 mm from the CEJ because implants have been suggested to be placed apico-coronally, 2 to 3 mm below the adjacent CEJ. 22 The topology (right and left sides) and sex did not influence the overall measurements. However, a significantly lower buccal bone thickness and a significantly higher lingual bone thickness in females were observed with regard to first premolars.…”
Section: Discussionmentioning
confidence: 91%